La “subversión científica” en las universidades de Argentina e Hispanoamérica - Laura Graciela Rodríguez (Centre de Recherches sur les Mondes Américains, 2016)
This article will discuss, based on the study of the magazine Verbo of Argentina during the years of the dictatorship (1976-1983), ideas that Catholics from right about the universities and centers of research of Argentina in particular, and Latin America had in general. Verbo was the organ of diffusion of the organization called Ciudad Católica which had origins in France and international ramifications. More precisely, in this paper we show how these Catholics who wrote in Verbo – clerics, Argentines and foreigners, attempted to “collaborate” with “anti-subversive fight” that was going on, denouncing, on the one hand, the “advancement” of “communism” among scientists and universities in Argentina and “Latin America”; and on the other hand, the “penetration Marxist” within the Catholic universities.